Ocular presentations and toxoplasma serology - Nor, Zurainee Mohamed; Abdullah, Khairul Anuar; Fong, Mun Yik; Hoh, H.B. (Faculty of Medicine, University of Malaya, 2000)
During the period 1996-1998, 134 patients suspected of having ocular toxoplasmosis were seen in the Ophthalmology Clinic of the University Hospital, Kuala Lumpur. Clinical presentations in these patients ranged from poor vision to severe retinal detachment. Of these patients, 72% were confirmed positive for Toxoplasma gondii; infection by serological methods. Chorioretinjtis and vitritis were found to be the most apparent symptoms, both having 100% correlation with serological positivity, This was followed by uveitis, floaters, and retinal detachment with correlation at 78%, 75% and 75%, respectively. However, there was no correlation between level of serotitre and ocular presentations.